Aesthetics measurement of hearing aids through eye tracking: a contribution of design for inclusion (Human Factors in Design, 2020)
The product’s aesthetic characteristics influence the user’s interactions with them, as well as they can change the meanings attributed to the products. When it comes to assistive technologies, these associations can lead to reinforcing the stigma of disability related to its users. Therefore, this research aimed to measure the visual aesthetic experience with three different models of hearing aids, using the eye-tracking method. Thus, identifying how aesthetic principles behave in hearing aids, according to the visual patterns identified. In addition to eye tracking, a questionnaire was used to obtain data about the subjects. As main results, greater preference was expressed for the model with a higher degree of novelty, as well as it was possible to verify greater concentration of the eye gaze in the models of hearing aids  referred by the subjects. In addition,  he results corroborate with the  iterature identifying relationships  etween duration of fixations and  roportion, as well as number of fixations and pureness. Therefore, when measuring aesthetic experience in an objective way, one can understand cognitive and affective aspects of the interaction with hearing aids.
Keywords: Aesthetics; Assistive technology; Design; Eye-tracking; Hearing aid